2020
DOI: 10.1101/2020.12.21.20248643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and immunogenicity clinical trial of an inactivated SARS-CoV-2 vaccine, BBV152 (a phase 2, double-blind, randomised controlled trial) and the persistence of immune responses from a phase 1 follow-up report

Abstract: BackgroundBBV152 is a whole-virion inactivated SARS-CoV-2 vaccine (3 µg or 6 µg) formulated with a Toll-like receptor 7/8 agonist molecule adsorbed to alum (Algel-IMDG). Earlier, we reported findings from a phase 1 (vaccination regimen on days 0 and 14) randomised, double-blind trial on the safety and immunogenicity of three different formulations of BBV152 and one control arm containing Algel (without antigen). Two formulations were selected for the phase 2 (days 0 and 28) study. Here, we report interim findi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Three Chinese conglomerates and one Indian company have used the tried-and-true method of viral inactivation by β-propriolactone treatment, along with various alum adjuvants for generation of their SARS-CoV-2 vaccine candidates [36][37][38][39][40][41][42]. Each is using the prime-boost regimen with 4-6 μg virus and 14-28 days separation between prime and booster injections.…”
Section: Inactivated Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…Three Chinese conglomerates and one Indian company have used the tried-and-true method of viral inactivation by β-propriolactone treatment, along with various alum adjuvants for generation of their SARS-CoV-2 vaccine candidates [36][37][38][39][40][41][42]. Each is using the prime-boost regimen with 4-6 μg virus and 14-28 days separation between prime and booster injections.…”
Section: Inactivated Virusmentioning
confidence: 99%
“…Ad5 21 d.a.) [30] Post dose 1 Notes: The most common solicited local and systemic reactogenicity were pain at the injection site, and headache, and these have been reported in Table 2 Table 3 in reference [42].…”
Section: Mrna Vaccines-safety/reactogenicity and Immunogenicity/efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The sero-conversion rate with neutralizing antibodies (NAb) following vaccination with BBV152 was 99.6%. 5 Here, we present the NAb titers (PRNT 50 ) of sera collected from vaccine recipients, who had received BBV152 vaccine-candidate in phase-II trial 4 Andreano E et al reported an escape of the UK-variant with E484K substitution, which was followed by an 11-amino-acid insertion in the NTD N5 loop (248aKTRNKSTSRRE248k) from high NAb in convalescent plasma, which was a serious concern pertaining to the potential efficacy of the vaccines. 7 Our study evidently highlighted comparable neutralization activity of vaccinated individuals sera against variant as well as heterologous SARS-CoV-2 strains.…”
mentioning
confidence: 99%
“…They are done to retrospectively diagnose a case that could have been missed during its initial acute phase [3]. Actual reinfection from the same strain of coronavirus disease 2019 (COVID- 19) has often been questioned since many issues related to technical errors during sample collection, timing of collection, type of sample used, and false negative or positive results while performing the reverse transcription-polymerase chain reaction (RT-PCR) method [4]. In this case report, we discuss a reinfected case of COVID-19 despite having circulating antibodies.…”
Section: Introductionmentioning
confidence: 99%